Enzyme tests in the evaluation of thrombolysis in acute myocardial infarction. Issue 2 (February 1988) - de Zwaan, C; Willems, G M; Vermeer, F; Res, J; Verheugt, F W; van der Laarse, A; Simoons, M L; Lubsen, J; Hermens, W T
Abstract : The activity of alpha-hydroxybutyrate dehydrogenase, creatine kinase, creatine kinase MB and aspartate aminotransferase was measured on serial plasma samples from patients with acute myocardial infarction. The study was part of a multicentre randomised trial of the effect of thrombolytic treatment in the acute phase of acute myocardial infarction. The applicability and comparability of enzyme tests for the estimation of myocardial injury were studied in 76 control patients and 74 patients treated with streptokinase. Treatment with streptokinase caused a considerable acceleration of enzyme release after acute myocardial infarction, both in patients with persistent coronary occlusion and in those with successful reperfusion. But this changed pattern of enzyme release did not affect the rate of enzyme elimination from plasma or the released proportions of different enzymes. Thus the assessment of infarct size by measurement of these enzyme activities can also be applied to patients treated with streptokinase. Moreover, the enzymes measured in the present study are all equally valid markers of myocardial injury.